Моделювання стратегічних цілей розвитку суб’єктів харчової промисловості у макроекономічної середовищі - Шеремет, Олег Олексійович (My University, 2019)
У статті розглядаються питання щодо моделювання стратегічних цілей розвитку суб’єктів харчової промисловості у макроекономічному середовищі. Сформована ієрархія взаємопов’язаності місії, стратегічних орієнтирів та цілей суб’єктів харчової промисловості. Розроблена модель функціонування та стратегічного розвитку суб’єкта харчової промисловості. Запропоновано визначення основних аспектів, які необхідно враховувати при формуванні стратегічних цілей у харчовій промисловості. Представлена ієрархія стратегічних цілей розвитку суб’єктів харчової промисловості. Обґрунтовано та запропоновано моделювання стратегічних цілей розвитку суб’єктів харчової промисловості у макроекономічному середовищі. Досліджено класифікацію стратегічних цілей розвитку суб’єктів харчової промисловості у макроекономічному середовищі. Сформовані концептуальні підходи до розробки програми реалізації стратегічних цілей у харчовій промисловості. Запропонований підхід надає можливість дослідити процес розробки програми реалізації стратегічних цілей у харчовій промисловості, враховуючи систему забезпечення, яка включає принципи, критерії, параметри, обмеження та відповідну спрямованість, фактори впливу та їх узгодженість, що дозволить виокремити альтернативні шляхи досягнення стратегічних цілей та сформувати методичне і ресурсне забезпечення з метою отримання ефективних результатів за умови заданих параметрів. The article deals with the questions of modeling strategic goals of development of food industry subjects in the macroeconomic environment. A hierarchy of interconnected missions, strategic benchmarks and goals of food industry actors has been formed. The model of functioning and strategic development of the subject of the food industry is developed. It is proposed to identify the main aspects that need to be taken into account when formulating strategic goals in the food industry. A hierarchy of strategic goals for the development of food industry subjects is presented. The classification of strategic goals of development of food industry subjects in the macroeconomic environment is researched. The methodological basis of the paper is the complex of methods, including methods of scientific cognition, analysis and synthesis, systematization and scientific abstraction. The information basis of the conducted researches is the scientific work of domestic and foreign scientists in the field of realization of market strategies in the subjects of the national economy. The conceptual approaches to the development of a program for the implementation of strategic goals in the food industry are formed. The proposed approach provides an opportunity to explore the process of developing a program for the implementation of strategic goals in the food industry, taking into account the provision of a system that includes principles, criteria, parameters, constraints and appropriate direction, factors of influence and their coherence, which will allow to identify alternative ways to achieve strategic goals and form methodological and resource support for the purpose of obtaining effective results subject to specified parameters. Practical importance of the modeling of strategic goals of development of food industry subjects in the macroeconomic environment is substantiated and proposed.
Keywords: кафедра економіки праці та менеджменту; інтеграція; національна економіка; макроекономічне середовище; strategy; integration; national economy; macroeconomic environment